The dragon painter [1919] - Worthington, William (Harrington Park, N.J. : Milestone Film & Video, 2008)
The wrath of the gods, or, the destruction of Sakura-Jima (1914) / scenario by Thomas H. Ince and William Clifford ; produced by Thomas H. Ince ; directed by Reginald Barker ; special effects by Raymond B. West ; a film of the George Eastman House Motion Picture Study Collection ; musical score composed by Marco Lienhard (60 min.)##Screen snapshots issue no. 20 (1921) / produced by Jack Cohn and Louis Lewyn (3 min.).
Silent, with English subtitles.
film
Keywords: Worthington, William